Most accurate mutations in SARS-CoV-2 genomes identified in Uzbek patients show novel amino acid changes - Ayubov, Mirzakamol S.; Mirzakhmedov, Mukhammadjon K.; Yusupov, Abdurakhmon N.; Asrorov, Akmal M.; Nosirov, Bakhtiyor V.; Usmanov, Dilshod E.; Shermatov, Shukhrat E.; Ubaydullaeva, Khurshida A.; Abdukarimov, Abdusattor; Buriev, Zabardast T.; Abdurakhmonov, Ibrokhim Y. (Frontiers in Medicine, 2024)
The rapid changes in the coronavirus genomes created new strains after the first variation was found in Wuhan in 2019. SARS-CoV-2 genotypes should periodically undergo whole genome sequencing to control it because it has been extremely helpful in combating the virus. Many diagnoses, treatments, and vaccinations have been developed against it based on genome sequencing. With its practical implications, this study aimed to determine changes in the delta variant of SARS-CoV-2 widespread in Uzbekistan during the pandemic by genome sequencing, thereby providing crucial insights for developing effective control strategies that can be directly applied in the field. Design: We meticulously generated 17 high-quality whole-genome sequence data from 48 SARS-CoV-2 genotypes of COVID-19 patients who tested positive by PCR in Tashkent, Uzbekistan. Our rigorous approach, which includes stringent quality control measures and multiple rounds of verification, ensures the accuracy and reliability of our findings. Methods: Our study employed a unique combination of genome sequencing and bioinformatics web tools to analyze amino acid (AA) changes in the virus genomes. This approach allowed us to understand the genetic changes in the delta variant of SARS-CoV-2 widespread in Uzbekistan during the pandemic. Results: Our study revealed significant nucleotide polymorphisms, including nonsynonymous (missense) and synonymous mutations in the coding regions of the sequenced sample genomes. These findings, categorized by phylogenetic analysis into the G clade (or GK sub-clade), contribute to our understanding of the delta variant of SARS-CoV-2 widespread in Uzbekistan during the pandemic. A total of 134 mutations were identified, consisting of 65 shared and 69 unique mutations. These nucleotide changes, including one frameshift mutation, one conservative and disruptive insertion-deletion, four upstream region mutations, four downstream region mutations, 39 synonymous mutations, and 84 missense mutations, are crucial in the ongoing battle against the virus. The comprehensive whole-genome sequencing data presented in this study aids in tracing the origins and sources of circulating SARS-CoV-2 variants and analyzing emerging variations within Uzbekistan and globally.